Central African Economic and Monetary Community (CEMAC) : Common Policies in Support of Member Countries Reform Programs. (IMF Staff Country Reports; Country Report ;, 2019)
The regional strategy has helped stabilize the regional economic position thanks to large fiscal consolidation efforts, a tighter monetary policy, and external financial assistance. The external position improved, and external reserves picked up. However, the region remains dependent on oil revenues, with little progress in economic diversification, under-performing budget non-oil revenues and weaknesses in the financial sector. The policy assurances included in BEAC's letter of December 2018 were implemented as planned and the CEMAC authorities reiterated their full commitment to the strategy and their readiness to implement additional corrective measures if needed. Progress was made towards new IMF-supported program in Congo and Equatorial Guinea.